Study on Metakaolin Impact on Concrete Performance of Resisting Complex Ions Corrosion - Xupeng, Chen; Zhuowen, Sun; Jianyong, Pang (Frontiers in Materials, 2021)
the tests conducted in this study are mainly to verify the Metakaolin (MK) impacts on the concrete durability when the concrete suffers joint corrosion by SO42-,Mg2+ and Cl-. A total of 4 groups of concrete test blocks with different MK contents are tested to see their physical property changes and macro-morphology differences during the cyclic process. And a series of approaches, including XRD,FTIR,SEM, and EDS, are applied to study the concrete phase composition changes and the micro-morphology features of all groups. The results show that, when reaching 20 cycles, the concrete mixed with 10% MK shows the best concrete physical properties; when reaching 120 cycles, the concrete with 5% MK admixture shows the best durability, produces corrosion products in quantity similar to ordinary concrete, presents relatively compacted micro-structure and small internal porosity. Mg2+ actually has a great impact on Metakaolin. The corrosion product quantity increases significantly when MK admixture reaches 15%. The great number of produced M-S-H makes the corrosive ions damage the concrete for a second time, leading to serious aggregate peeling-off, powder surface of test block, and porous micro-structure.